2016
DOI: 10.1007/s10461-016-1593-5
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Risk Behaviors Among HIV-Infected Persons in St. Petersburg, Russia

Abstract: We analyzed baseline data from an observational cohort of HIV-infected ART-naïve patients in St. Petersburg, Russia to explore whether pain was associated with HIV risk behaviors. The primary outcomes were (1) unprotected vaginal or anal sex in the past 90 days and (2) sharing of needles or equipment in the past month. Secondary outcomes included: use of alcohol prior to sex, current injection drug use, number of unprotected sex and sharing episodes, and days injected in the past month. The main independent va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Associations with substance use have also been reported [8,38,39], with pain serving both as a mediator and as a predictor of more use of recreational drugs, as well as more depressive symptoms [46]. Other negative effects of pain include direct associations with reduced social support [26] and with higher rates of unprotected vaginal or anal sex [29], raising concern that pain in PLWH may also lead to worse outcomes on ART. Whilst we were unable to consider this association in our cross-sectional analysis (the majority of POPPY participants were on stable ART at recruitment), Surratt [7] reported that those with untreated pain had a 42% lower odds of 95% medication adherence in the previous week compared to those who were pain-free.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations with substance use have also been reported [8,38,39], with pain serving both as a mediator and as a predictor of more use of recreational drugs, as well as more depressive symptoms [46]. Other negative effects of pain include direct associations with reduced social support [26] and with higher rates of unprotected vaginal or anal sex [29], raising concern that pain in PLWH may also lead to worse outcomes on ART. Whilst we were unable to consider this association in our cross-sectional analysis (the majority of POPPY participants were on stable ART at recruitment), Surratt [7] reported that those with untreated pain had a 42% lower odds of 95% medication adherence in the previous week compared to those who were pain-free.…”
Section: Discussionmentioning
confidence: 99%
“…Among PLWH, pain is associated with poorer adherence to ART [20,21], higher rates of viral load rebound [22], treatment switching [23,24] and, in some subgroups, missed clinic visits [25]. Furthermore, PLWH in pain are more likely to experience lack of social support [26] and to be involved in risky behaviours such as alcohol use, intravenous drug use and sexual risk taking [6,[27][28][29][30]. Thus, in addition to the burdens placed on both the individual and the healthcare/social system, pain in PLWH has the potential to seriously curtail attempts to eliminate new HIV infections.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, findings relating to ART exposure are likely to differ in this cohort to those from cohorts of newly diagnosed individuals starting cART. In Koeppe's study of PWH diagnosed with chronic pain, cART was associated with decreasing rates of pain over a median follow-up period of 5.2 years [13]. Among PWH attending a routine outpatient appointment in the UK in 2007 [14], the only HIV factors significantly associated with current pain in multivariable analyses were a longer time since HIV diagnosis and current receipt of a PI.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic pain is a common and significant problem for people with HIV (PWH). It affects up to 83% of PWH, and is associated with functional disability [1], frailty [2], high resource utilization [3,4], reduced quality of life [4], poor retention in care [5,6], suboptimal antiretroviral therapy (ART) adherence [5], and risk behaviors that can transmit HIV to others [[7], [8], [9], [10]]. Past enthusiasm for opioids as a treatment for chronic pain and under appreciation of their risks has created a large group of “legacy patients” who have been maintained on chronic opioids for pain, sometimes for years [11,12].…”
Section: Introductionmentioning
confidence: 99%